2003
DOI: 10.1007/s00259-002-1097-6
|View full text |Cite
|
Sign up to set email alerts
|

Dual-modality PET/CT imaging: the effect of respiratory motion on combined image quality in clinical oncology

Abstract: To reduce potential mis-registration from differences in the breathing pattern between two complementary PET and CT data sets, patients are generally allowed to breathe quietly during a dual-modality scan using a combined PET/CT tomograph. Frequently, however, local mis-registration between the CT and the PET is observed. We have evaluated the appearance, magnitude, and frequency of respiration-induced artefacts in CT images of dual-modality PET/CT studies of 62 patients. Combined PET/CT scans during normal re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
138
0
5

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 270 publications
(145 citation statements)
references
References 10 publications
0
138
0
5
Order By: Relevance
“…( 11 , 13 , 14 ) It has been reported that using CT data acquired at deep inspiration can produce severe artifacts, ( 15 ) and also that CT protocols using normal expiration breath‐hold or partial breath‐hold acquisition can reduce artifacts in this region. ( 15 , 16 ) Others have proposed that errors due to attenuation correction can be reduced by using a Cine‐CT to produce an averaged (or max) image dataset for correction purposes. ( 17 – 20 ) …”
Section: Introductionmentioning
confidence: 99%
“…( 11 , 13 , 14 ) It has been reported that using CT data acquired at deep inspiration can produce severe artifacts, ( 15 ) and also that CT protocols using normal expiration breath‐hold or partial breath‐hold acquisition can reduce artifacts in this region. ( 15 , 16 ) Others have proposed that errors due to attenuation correction can be reduced by using a Cine‐CT to produce an averaged (or max) image dataset for correction purposes. ( 17 – 20 ) …”
Section: Introductionmentioning
confidence: 99%
“…This can produce a mis-registration between the CT data used to perform attenuation correction and the PET emission data which is acquired over many respiratory cycles. There have been several studies showing that this effect can cause artifacts in PET/CT reconstructions in oncology -especially at borders between the lung and soft tissue, such as the liver-lung interface [1][2][3][4][5][6]. Because the heart also has a lung-soft tissue interface, it would seem likely that there would be similar artifacts in apparent myocardial activity uptake when performing cardiac PET/CT studies.…”
Section: Introductionmentioning
confidence: 99%
“…The image of a certain slice is thus recorded in fractions of a second, and a moving tumor will likely not be imaged at its average position, given the average duration of a full respiration cycle (4 s) (5). A PET scan, on the other hand, will take 2-5 min per bed position, resulting in a distortion of the combined PET/CT image (6,7). Furthermore, respiratory motion could lead to blurring of the PET image and consequently to uncertainties in tumor size, position, and shape of the tumor and an underestimation of the measured standardized uptake value (SUV) (8,9).…”
mentioning
confidence: 99%